Real-world evidence on the association of novel antidiabetic medication use with cancer risk and protective effects: a systematic review and network meta-analysis - Ahmed S. Kenawy; Yi-Shao Liu; Ayobami Aiyeolemi; Godwin Okoye; Chanhyun Park (Therapeutic Advances in Drug Safety)
Background: Novel antidiabetic medications (SGLT-2 inhibitors, DPP-4 inhibitors, and GLP-1 agonists) are commonly used worldwide; however, the available research lacks definitive conclusions on their protective effects or potential risks on cancer. Objectives: Compared to other antidiabetics, our systematic review and network meta-analysis (NMA) aims to use real-world studies to assess the potential cancer risks or protective effects of these novel antidiabetics. Methods: We comprehensively searched PubMed, CINAHL, and Web of Science from their inception until November 30, 2023. We included observational studies examining at least one novel antidiabetics in the systematic review. The novel antidiabetics include sodium-glucose cotransporter-2 inhibitors (SGLT-2i), dipeptidyl peptidase-4 inhibitors (DPP-4i), and glucagon-like peptide-1 agonists (GLP-1a). Design: We focused on cohort studies that provided data on cancer incidence and sample size in the NMA. Using NetMetaXL ® , the random effects model with informative priors was used in the NMA to estimate the pooled odds ratio (OR) with 95% credible intervals (CrI). Results: The systematic review included 62 studies, of which 22 met the inclusion criteria for the NMA. SGLT-2i users had lower overall cancer risk compared to sulfonylureas (OR: 0.54; 95% CrI: 0.40–0.74, low certainty), GLP-1a (OR: 0.70; 95% CrI: 0.53–0.92, low certainty), and DPP-4i users (OR: 0.72; 95% CrI: 0.57–0.92, very low certainty). DPP-4i users also had a lower cancer risk than sulfonylureas users (OR: 0.76; 95% CrI: 0.60–0.96, low certainty). No other statistically significant ORs were found in other direct comparisons. Conclusion: SGLT-2i users have a lower risk of developing cancers than sulfonylureas, GLP-1a, and DPP-4i users. These results may improve patient safety by guiding future clinical practice and medication choices. Future studies should investigate the mechanisms behind these observed associations. Trial registration: This NMA was registered in PROSPERO (CRD42023469941).